Methods for preserving bone marrow for autologous transplantation. - da Costa, F L (1992)
For Autologous Bone Marrow Transplantation (ABMT) the patient's own marrow is harvested before myelotoxic high-dose radio-chemotherapy and later returned to promote hemopoietic reconstitution. Between harvest and return the bone marrow must be preserved. The time elapsed between harvest and return depends on the intended therapy. Although--bone marrow may keep its hematopoietic potential for a few days without freezing, preservation for longer periods imposes the need for cryopreservation. Some of the current methods for marrow preservation are reviewed, with special emphasis given to cryopreservation. Hospital de Santa Maria Bone Marrow Transplant Unit cryopreservation method is described.